DISCURSIVE STRATEGIES OF IDEOLOGICAL REPRESENTATIONS IN POLITICAL SPEECHES: A CRITICAL DISCOURSE ANALYSIS OF SELECTED SPEECHES OF KWAME NKRUMAH - Aikins Addae; Daniel Arkoh Fenyi; Hamidu Alhassan (Universitas Muhammadiyah Prof. DR. HAMKA, 2021)
To win political power, political actors sometimes adopt linguistic and rhetorical strategies that enable them to communicate effectively with their audience. This makes the study of the language of politics an interesting academic exercise. Earlier studies on political speeches, in Ghana, especially, have tended to be a description and an analysis of style, innovative and persuasive strategies of politicians and the manipulation of linguistic structures to champion individual interest in presidential speeches. Not much has been done in terms of the functional implications of these rhetorical devices. This study therefore attempted a critical discourse analysis of selected speeches of Kwame Nkrumah to investigate the role of language in creating ideology and sustaining power as well as ideological discursive structures in political speeches. The study specifically investigated linguistic expressions which carry these ideological colourations in the speeches under review. The study employed the qualitative research approach and textual analysis as the design. The sampling method was purposive, and the analysis was done thematically. The study employed the theoretical frameworks of Fairclough’s CDA and Van Dijk’s socio-cognitive approach to analyse the speeches. The study revealed that the ideologies were carried out through these discursive structures: evidentiality, pronouns, agency, metaphor, intertextuality, rhetorical question and strong modal of obligation. The study also revealed that Nkrumah relies on language to produce ideologies of nationalism, patriotism, national self-image, hope, power and dominance in his speeches. The study further revealed that the discursive structures produce and sustain power and unequal power relations between Nkrumah and his audience. The study afforded much evidence to conclude that politics is a game that can be successfully played through a skillful employment of language. The study, therefore, concludes that the speeches that were analysed were used as a means of establishing, maintaining, and sustaining power and asymmetrical power relations. Keywords: rhetorical devices, linguistic structures, persuasive strategies, ideologies, discursive structures